Resíduo seco de destilaria com solúveis (DDGS) na alimentação de frangos de corte - Schöne, Rodrigo André (2015)
The objective of this study was to determine the energy value and the amino acids digestibility of dried distillers grains with solubles (DDGS), and evaluate the effect of inclusion of DDGS on performance and carcass yield of broilers in the growing and finishing phases. Two experiments were conducted, at first a bioassay of total excreta collection was conducted in order to calculate the apparent metabolizable energy (AME) and AME corrected for nitrogen balance (AMEn) and the coefficient of apparent metabolizable energy (CAM) and CAM corrected for nitrogen balance (CAMn). A total of 48 Cobb 21-days-old male broilers were used, with an average weight of 932g ± 45g. The experimental design was completely randomized with two treatments, being one the reference diet (RR) and other with 20% DDGS, with 6 replicates totaling 12 experimental units with four broilers each. At the end of the experiment the amount of feed consumed by experimental unit was determined and the total amount of excreta produced. Through the results of laboratory tests values of AME, AMEn, CAM and CAMn were calculated. In a second trial, 12 adult cecectomized Leghorn roosters were used, with average weight of 1,912.1 ± 133.73 g, using the forced feeding technique. Six birds ingested food test (DDGS) and six birds were fasted to determine the metabolic and endogenous losses used to calculate the true digestibility coefficients. Obtained the values of amino acids ingested and excreted and after know its endogenous and metabolic fraction the digestibility coefficients of each amino acid were determined. The values of AME, AMEn, CAM and CAMn of DDGS obtained in this study were 2,461kcal/kg, 2,282kcal/kg, 51.37% and 47.63%, respectively. The total amino acid values ranged from 0.180% to 3.370% for tryptophan and leucine, respectively. The digestibility coefficients varied between 89.17% (lysine) to 97.01% (leucine). In the second experiment, 900 Cobb Slow 21-days-old broilers were distributed in a completely randomized design, factorial 2 x 5, totaling 10 treatments (5 DDGS inclusion levels and 2 genders), with five replicates and 18 birds each. The DDGS levels studied were 0; 5; 10, 15 and 20% of inclusion in the experimental diets. At 35 and 45 days old the birds were weighed, as well as the remains of feed to obtain the performance variables. At 45 days old carcass yield was evaluated. There was no interaction (P>0.05) between sex and levels DDGS inclusion on performance of broilers from 21 to 35 days old. Feed intake was higher (P<0.05) for males, however, DDGS inclusion level did not affect (P>0.05) the feed intake of the birds. The weight gain reduced (P<0.05), however feed conversion ratio improved by the inclusion of 3.27% DDGS. There was no interaction (P>0.05) between sex and levels of DDGS inclusion in broiler rations from 21 to 42 days old. Feed intake was higher (P<0.05) for males and feed intake decreased (P<0.05) for males and females as the inclusion of DDGS increased. Feed conversion was lower for males (P<0.05) and increased (P<0.05) as levels of DDGS raised in diets, regardless of gender. Weight gain was higher for males (P<0.05) and reduced (P<0.05) as DDGS level in feed increased, for males and females. There was no interaction (P>0.05) between DDGS inclusion levels and sex of broilers for carcass yield and cuts yield. The higher was the inclusion of evaluated food the lower was the carcass yield (P<0.05). Breast yield, wing, thigh and drumstick showed no significant effect (P>0.05). Females had higher amount of abdominal fat (P<0.05). The inclusion of DDGS in the feed of broilers from 21 to 35 days old to the level of 3.27% improves feed conversion. In the period from 21 to 42 days, the inclusion of DDGS in diets showed a negative effect on the performance of broilers. Between 35 and 45 days of age, the use of DDGS reduced carcass yield of broilers and promoted greater abdominal fat in females